ACADEMIC MOTIVATION, PARENTAL EDUCATION AND WRITING ACHIEVEMENT OF ENGLISH STUDY PROGRAM STUDENTS, SRIWIJAYA STATE POLYTECHNIC - Sri Endah Kusmartini (Politeknik Negeri Sriwijaya, 2012)
This study examined the correlation of academic motivation and parental education towardswriting achievement of English Study Program students, Sriwijaya State Polytechnic in academic year2012/2013. The Study also examined whether there was a significant difference in terms of gendertowards writing achievement of the students. It was quantitative correlational research. The sampleconsisted of 45 students of English Study Program, Sriwijaya State Polytechnic. Academic MotivationScale (AMS) by Vallerand et al. (1992) with some modification conducted by researcher was used as ameasure to find out the academic motivation of the students and demographic questionnaire was usedto find out name, class, gender and parental education of the students. Meanwhile, the data aboutwriting achievement of the students were taken from the archive in English Study Program, SriwijayaState Polytechnic. The results showed that academic motivation added to parental education correlatedsignificantly towards writing achievement of the students (R=0.837); and there was no significantdifference in terms of gender towards writing achievement of the students. Hopefully, future studies will investigate why and how academic motivation added to parental education influenced and gavecontribution to writing achievement of the students.